A postcolonial moment or colonial subcontractor? - Tariq Dana (17733705) (2024)
Colonial and settler-colonial studies broadly agree that colonialism, anti-colonialism, decolonization and postcolonialism form a path-dependent chain. However, can the conditions of anti-colonialism and postcolonialism coexist in an ongoing context of settler-colonialism? Somdeep Sen answers this puzzling question by interrogating the nature of Hamas’ presence in Gaza. He concludes that while Hamas is a militant movement engaged in anti-colonial struggle, it has also built governance structures and institutions, resembling postcolonial statecraft. Nevertheless, for Sen, it is not either/or: he cautiously frames the coexistence between anticolonialism and postcolonialism within the long and complex path toward liberation. Other Information Published in: International Politics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41311-024-00572-x